Acute Toxicity and Gastroprotective Role of M. pruriens in Ethanol-Induced Gastric Mucosal Injuries in Rats. (28th May 2013) - Golbabapour, Shahram; Hajrezaie, Maryam; Hassandarvish, Pouya; Abdul Majid, Nazia; Hadi, A. Hamid A.; Nordin, Noraziah; Abdulla, Mahmood A.
Abstract : The investigation was to evaluate gastroprotective effects of ethanolic extract of M. pruriens leaves on ethanol-induced gastric mucosal injuries in rats. Forty-eight rats were divided into 8 groups: negative control, extract control, ulcer control, reference control, and four experimental groups. As a pretreatment, the negative control and the ulcer control groups were orally administered carboxymethylcellulose (CMC). The reference control was administered omeprazole orally (20 mg/kg). The ethanolic extract of M. pruriens leaves was given orally to the extract control group (500 mg/kg) and the experimental groups (62.5, 125, 250, and 500 mg/kg). After 1 h, CMC was given orally to the negative and the extract control groups. The other groups received absolute ethanol. The rats were sacrificed after 1 h. The ulcer control group exhibited significant mucosal injuries with decreased gastric wall mucus and severe damage to the gastric mucosa. The extract caused upregulation of Hsp70 protein, downregulation of Bax protein, and intense periodic acid schiff uptake of glandular portion of stomach. Gastric mucosal homogenate showed significant antioxidant properties with increase in synthesis of PGE2, while MDA was significantly decreased. The ethanolic extract of M. pruriens leaves was nontoxic (<5 g/kg) and could enhance defensive mechanisms against hemorrhagic mucosal lesions.